Properties of Schist Extracted in the City of Denizli Surroundings as Construction Material - Saffet Yağız (Pamukkale University Journal of Engineering Sciences, 2011)
There are various type of building stone extracted at stone quarries in the city of Denizli surroundings. Travertine, limestone and schist quarries are the most common in the area. Schist that is one of the units of Menderes massive is the main natural stone sources in Çal, Bekilli and Baklan Triangle in the northeast of the City. The aim of this study is to investigate the usability of schist stone as building stone quarried in the area. To obtain the aim, geological investigations were conducted in the field and representative samples were collected from the quarries. On the samples, petrograpical, mineralogical (XRD), chemical (XRF) analysis and geomechanical test (i.e., uniaxial compressive strength, Schmidt hardness, water absorption by weight, effective porosity, fullness ratio, flexural strength, sonic wave velocity, modulus of elasticity, natural and saturated unit weight) were conducted and the usability of schist stone as building stone have been studied by evaluating obtained findings. Analysis and relevant tests were conducted in accordance with international standards and procedures. Concluding remark is that quarried schist stone in the area are acceptably good as building stone to be used for both interior and exterior of construction building and outdoors as coverage material.